Caracterização óptica on-line das misturas dispersiva e distributiva na extrusão dupla rosca - Bernardo, Felipe Oliveira Campos (2022)
In this work, the effect of different kneading blocks on the dispersive and distributive mixing levels of a diluted PS/PA6 mixture along the screw profile of a twin-screw extruder was investigated via online monitoring of optical properties. Complementarily, were studied the rheo-optical characteristics of the matrix (PS), as well as the effect of shearing on the non-isothermal crystallization of the dispersed phase (PA6), in pure state and in a PP/PA6 mixture, conducted on a CSS450 hot shear system of a light polarized optical microscope (MOLP). Off line thermal and rheological measurements were also performed. In the extrusion, measurements were conducted in transient state, with the addition of a tracer and the transmitted light intensity collected and quantified in terms of turbidity and birefringence. Three different screw configurations were studied. The influence of different screw rotation speeds and barrel temperature on the mixture was also investigated. Rheological measurements indicated viscosity ratios between the polymers unfavorable to the breakage of the second phase droplets. MOLP analyzes indicated that higher shear rates increase PA6 crystallization and change the phase morphology from spherical to elongated, even at moderate rates of 10 s-1, in addition, PS birefringence increased with increasing shear rate and thermal reduction. Higher PA6 content in PS reduced the birefringence, as the polymers have polarizability with opposite signs. Extruder analyzes showed better levels of dispersive and distributive mixing for kneading elements with angles of 90° between their disks in relation to kneading elements with angles of 45° between their disks at the evaluated temperatures and screw speeds. The thickness of the 45° disks had no effect on mix levels.